Accounting for Social Responsibility in Small and Medium-Sized Enterprises - Mouloua, Mourad (Finance and Business Economies Review, 2021)
The objective of the study was to highlight accountability of social responsibility and to stand up to its various problems, highlighting the role it plays in serving society, the environment, employees, as well as workers, as well as the various requirements for applying social responsibility accounting; The study reached a number of results, the most important of which is that accounting for social responsibility is used to measure the social performance of projects and that it should be disclosed in the financial reports, and the study pointed out that the organizations should be made aware of the concept and importance of social responsibility accounting, and work on preparing an accounting model for them. So it's easy to understand and apply at the lowest possible cost.